The Effect of Parkour Exercise in Athletics Training on Locomotor Skills in Elementary School Students - Rubby Syihabuddin; Indra Safari; Dewi Susilawati (Universitas Negeri Semarang, 2026)
The advancement of digital technology has induced a sedentary lifestyle in youngsters, adversely affecting the deterioration of fundamental motor abilities, particularly locomotor motions. On the other hand, conventional athletic training in schools is often considered uninteresting for students. The purpose of this study is to evaluate the impact of using parkour in athletic training on enhancing elementary school children' locomotor skills and to compare its efficacy with traditional training methods. This research employed an experimental methodology with a pretest-posttest control group design. The research sample comprised kids from Mandalaherang Elementary School, categorized into an experimental group (parkour-based learning) and a control group (traditional learning). The TGMD-2 (Test of Gross Motor Development - Second Edition) was employed to assess locomotor skills. Data analysis was conducted using normality tests, homogeneity tests, and N-Gain assessments. The findings indicated a notable enhancement in the locomotor abilities of the experimental group. The experimental group attained an average N-Gain score of 0.5031 (moderate category), but the control group achieved just 0.2065 (poor category). Alongside physical attributes, observations indicated an enhancement in students' self-confidence and problem-solving abilities when confronted with challenges. The integration of parkour into the elementary school athletics curriculum has proven to be more effective in enhancing students' locomotor skills compared to conventional teaching methods. Parkour can serve as an innovative learning medium that is interesting, challenging, and suited to the developmental characteristics of elementary school students.